Diastology in the intensive care unit: challenges for the assessment and future directions - Gonzalez, Filipe (2024)
© 2024 The Authors. Echocardiography published by Wiley Periodicals LLC. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.